USE OF VAC THERAPY IN THE TREATMENT OF PURULENT-DESTRUCTIVE LUNG DISEASES ON THE BACKGROUND OF DIABETES: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Khamdamov, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. To improve treatment results by developing and using innovative methods of purulent cavity sanitation in patients with acute purulent-destructive lung diseases using VAC therapy. Materials and methods. During 2018-2021, 82 patients with acute lung abscesses on the background of diabetes were treated in the department of purulent surgery and purulent surgical complications of diabetes at the multidisciplinary clinic of the Tashkent Medical Academy. Results. The general direction of treatment of patients with lung abscesses against the background of diabetes is complex antibiotic therapy using modern minimally invasive technology (VAC). When choosing a treatment method, we considered the nature of the pathological process and its localisation (peripheral and central location of the abscess, the presence or absence of rupture into the bronchial space). Its main task is to accelerate the evacuation of purulent contents using transthoracic drainage of the abscess cavity. It leaves a non-stick drainage tube with a hydrophilic polyurethane sponge and connects it to a vacuum container for collecting fluid. VAC-therapy 30-45 mm wire for 3 days. Conclusion. VAC- therapy application - sugary diabetes in the background lungs abscess in treatment purulent space short time inside cleaning and perifocal of infiltration decrease with inflammation process quickly eliminate to do help giving new is a method.